A New Elixhauser-based Comorbidity Summary Measure to Predict In-Hospital Mortality. Issue 4 (April 2015) - Thompson, Nicolas R.; Fan, Youran; Dalton, Jarrod E.; Jehi, Lara; Rosenbaum, Benjamin P.; Vadera, Sumeet; Griffith, Sandra D.
Abstract : Background: Recently, van Walraven developed a weighted summary score (VW) based on the 30 comorbidities from the Elixhauser comorbidity system. One of the 30 comorbidities, cardiac arrhythmia, is currently excluded as a comorbidity indicator in administrative datasets such as the Nationwide Inpatient Sample (NIS), prompting us to examine the validity of the VW score and its use in the NIS. Methods: Using data from the 2009 Maryland State Inpatient Database, we derived weighted summary scores to predict in-hospital mortality based on the full (30) and reduced (29) set of comorbidities and compared model performance of these and other comorbidity summaries in 2009 NIS data. Results: Weights of our derived scores were not sensitive to the exclusion of cardiac arrhythmia. When applied to NIS data, models containing derived summary scores performed nearly identically ( c statistics for 30 and 29 variable-derived summary scores: 0.804 and 0.802, respectively) to the model using all 29 comorbidity indicators ( c =0.809), and slightly better than the VW score ( c =0.793). Each of these models performed substantially better than those based on a simple count of Elixhauser comorbidities ( c =0.745) or a categorized count (0, 1, 2, or ≥3 comorbidities; c =0.737). Conclusions: The VW score and our derived scores are valid in the NIS and are statistically superior to summaries using simple comorbidity counts. Researchers wishing to summarize the Elixhauser comorbidities with a single value should use the VW score or those derived in this study. Abstract : Supplemental Digital Content is available in the text.